2016
DOI: 10.1111/ijac.12614
|View full text |Cite
|
Sign up to set email alerts
|

Engineered TiO2 and SiO2‐TiO2 films on silica‐coated glass for increased thin film durability under abrasive conditions

Abstract: Thin films durability is critical to retain its performance in real life applications. For automotive glass, further factors such as haze appearance developed under abrasive conditions become relevant to ensure the driver's visibility. Macroscopic abrasion resistance tests of TiO2/SiO2 and SiO2–TiO2/SiO2 thin films on soda‐lime silica (SLS) glass were performed according to an American standard for safety grazing. The purpose of this, was to increase the top active film durability in a bilayer system by unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Consequently this results in lower bandgap values also [15], hence more efficient use of the solar light in outdoor testing. Additionally, the presence of amorphous SiO 2 phase improves the adhesion of the layer to the glass and abrasion resistance [34,35], which is clearly seen in long-term tests performed in this study (Figure 3c at 90° and Figure 6).…”
Section: Resultsmentioning
confidence: 75%
“…Consequently this results in lower bandgap values also [15], hence more efficient use of the solar light in outdoor testing. Additionally, the presence of amorphous SiO 2 phase improves the adhesion of the layer to the glass and abrasion resistance [34,35], which is clearly seen in long-term tests performed in this study (Figure 3c at 90° and Figure 6).…”
Section: Resultsmentioning
confidence: 75%
“…Kesmez et al [42] emphasized that TiO2 thickness should be kept as low as possible by decreasing the Ti concentration in order to preserve the AR properties of SiO2 layer. Furthermore, the results of Ramirez-Garcia et al [46] showed that outer TiO2 layer of very small thickness (20-50 nm) still gives improved abrasion resistance and lower transmission haze to the resultant SiO2/TiO2 bilayers. If dense A-SiO2 film is used in the double-layer system, transmittance of the resultant stack falls to 87.1% by coating with 0.1 M TiO2 layer and further to 77.1% by coating with 0.2 M TiO2 layer.…”
Section: Development Of Double-layer Coatingsmentioning
confidence: 98%
“…Ramirez-Garcia et al reported the use of amorphous SiO 2 and amorphous TiO 2 on surface coatings [16]. The SiO 2 /TiO 2 layer enhances the durability and adhesion of coatings.…”
Section: Introductionmentioning
confidence: 99%